2017
DOI: 10.20875/makusobed.350559
|View full text |Cite
|
Sign up to set email alerts
|

Güzel Sanatlar Li̇sesi̇ Vi̇yola Eği̇ti̇mi̇nde Kullanilan Repertuvara Yöneli̇k Öğrenci̇ Görüşleri̇ - Opinions of Students for Viola Training Repertoire in Fine Arts High School

Abstract: Ülkemizdeki Güzel Sanatlar Lisesi Viyola Öğretim Programında uygulanan viyola çalgı eğitimi 4 senelik bir aşamayı kapsamaktadır. Viyolanın, batı müziği çalgısı olmasının da etkisiyle doğal olarak viyola eğitiminde uygulanan repertuvar daha çok batı müziği ağırlıklı olmaktadır. Araştırma öncesi öğretmenlerle yapılan ön görüşmelerde viyola eğitiminde uygulanan mevcut repertuvarlara ilaveten farklı müzik türlerindeki eserlerin kullanılmasın viyola eğitimine farklı bir heyecan getireceği belirtilmiştir. Bu konuda … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Studies of gifted students in the high schools which provide education in the arts and in sport have particularly focused on the arts and sport (Birgül & Nacakcı, 2019; Polat et al, 2018; Tanrıkulu & Kahraman, 2019) and have concentrated mostly on students’ expectations. Olgun (2019) studied students at Fine Arts High Schools in three separate provinces and reported that female students found the duration of the arts courses and theoretical courses provided throughout the art education insufficient, whereas male students regarded them as sufficient.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of gifted students in the high schools which provide education in the arts and in sport have particularly focused on the arts and sport (Birgül & Nacakcı, 2019; Polat et al, 2018; Tanrıkulu & Kahraman, 2019) and have concentrated mostly on students’ expectations. Olgun (2019) studied students at Fine Arts High Schools in three separate provinces and reported that female students found the duration of the arts courses and theoretical courses provided throughout the art education insufficient, whereas male students regarded them as sufficient.…”
Section: Introductionmentioning
confidence: 99%